2019
DOI: 10.1101/847319
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human ESCRT-III Polymers Assemble on Positively Curved Membranes and Induce Helical Membrane Tube Formation

Abstract: Endosomal sorting complexes required for transport-III (ESCRT-III) are thought to assemble in vivo inside membrane structures with a negative Gaussian curvature. How membrane shape influences ESCRT-III polymerization and conversely how ESCRT-III polymers shape membranes is still unclear. Here, we used human core ESCRT-III proteins, CHMP4B, CHMP2A, CHMP2B and CHMP3 to address this issue in vitro by combining membrane nanotube pulling experiments, cryo-electron microscopy, cryo-electron tomography and highspeed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 78 publications
2
18
0
1
Order By: Relevance
“…Recent in vitro studies of the yeast ESCRT-III proteins Vps2-Vps24-Snf7 50 and their human homologs 58 have also demonstrated positive curvature membrane remodeling activity -the same membrane orientation seen in our structures -despite their well-characterized negative membrane curvature deformation activity in vivo. While the significance of those in vitro observations remains to be fully elucidated, it appears that ESCRT-III assemblies are more versatile than previously realized.…”
Section: Discussionsupporting
confidence: 62%
“…Recent in vitro studies of the yeast ESCRT-III proteins Vps2-Vps24-Snf7 50 and their human homologs 58 have also demonstrated positive curvature membrane remodeling activity -the same membrane orientation seen in our structures -despite their well-characterized negative membrane curvature deformation activity in vivo. While the significance of those in vitro observations remains to be fully elucidated, it appears that ESCRT-III assemblies are more versatile than previously realized.…”
Section: Discussionsupporting
confidence: 62%
“…They can take a variety of shapes on membranes in vitro and in vivo, including rings, flat spirals, open and closed helices, as well as cones. Most intriguingly, different ESCRT-III subunits can copolymerize, and the shapes of single-subunit polymers can vary significantly from those of multisubunit polymers, even if they contain the same subunits [9,10,15,[20][21][22][23][24][25] (Figure 1C). Of note, the ESCRT-III cones are often observed in vivo in various functions [26][27][28], while in vitro, helices, rings, and spirals are more common.…”
Section: Modular Membrane Binding In Escrt-iii Subunitsmentioning
confidence: 99%
“…Several recent studies reported the formation of double-stranded and three-stranded ESCRT-III filaments [9,10,16,20,24,31,34]. The most intuitive consequence following the transition from a single-stranded to a multistranded filament is an increase of the overall polymer rigidity.…”
Section: Increase Of Rigidities By Copolymerizationmentioning
confidence: 99%
“…6a, c): (1) The growing Snf7 protofilament allows the lateral co-assembly of a Vps24 - Vps2 heterofilament. The two filaments presumably correspond to parallel filamentous structures seen in vitro (Mierzwa et al, 2017, Pfitzner et al, 2020, Moser von Filseck et al, 2020, Bertin et al, 2020, Banjade et al, 2019). (2) Vps24 and Vps2 both use positively charged amino acid residues in their helices α1 to interact with negatively charged amino acids in helix α4 of Snf7 protomers in the protofilament.…”
Section: Discussionmentioning
confidence: 95%
“…In vitro Snf7, Vps24, Vps2 and other ESCRT-III proteins, when combined with each other, or on their own, assemble into polymers with a range of different shapes: short filaments, rings, long spirals, helical filaments, sheets, tubular and dome like structures. Some of these polymers consist of parallel ESCRT-III filaments with the capacity to deform membranes (Henne et al, 2012, Pfitzner et al, 2020, Moser von Filseck et al, 2020, Bertin et al, 2020, Maity et al, 2019, Schoneberg et al, 2018, Goliand et al, 2018, McCullough et al, 2015, Shen et al, 2014, Cashikar et al, 2014, Guizetti et al, 2011, Bajorek et al, 2009, Ghazi-Tabatabai et al, 2008, Lata et al, 2008b, Hanson et al, 2008, Banjade et al, 2019). These experiments unambiguously demonstrate that ESCRT-III subunits self-assemble into heteropolymers with different shapes and distinct properties that can remodel membranes.…”
Section: Introductionmentioning
confidence: 99%